Evaluation of the performance and sustainability of smes operating in the agriculture and food sector within the framework of the pandemic - Cikmaz, Gul (Springer Science and Business Media Deutschland GmbH, 2024)
The covid-19 epidemic, which spreads around the world, continues to affect human life. In this process, taking some restrictions and measures such as continuing education from a distance, allowing curfew at certain hours, curfew on weekends, and implementing flexible working in workplaces to prevent the epidemic caused the lives of people to change. Due to these changes, it is thought that the epidemic, which causes anxiety in society, may have many effects, especially fear, psychologically after a certain time. In this process, one of the areas where the epidemic showed its effect was business life and the performance and sustainability of employees. The continued spread of the COVID-19 epidemic is vital for both people and businesses. Since the first time the issue of COVID-19 emerged, it has affected many areas of people such as economic, social, and psychological, and it is seen that it continues to affect it. As a result of the literature review, it has been seen that there are still many results related to COVID-19 research and studies that reveal the relationship with many situations. A number of evaluations have been made on the subject of COVID-19 and its results, and then the working hypotheses have been explained. It has been seen in theoretical and field studies in the literature that the continuation of COVID-19 has many effects and consequences for humans. For example; The effects of the Covid-19 epidemic on the sports sector, social media, global threats, the global economy, consumers’ purchasing habits, psychological effects, economic effects, anxiety, and fear levels have been investigated. In this sense, it is thought that COVID-19 significantly affects people's lives and continues to affect them, and it is assumed that it may have various consequences. The purpose of this research is to measure the performance and sustainability of SMEs operating in the agriculture and food sector during the COVID-19 pandemic period: Gaziantep and Chisinau are to conduct a research study. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Keywords: Agriculture sector; COVID-19; Food sector; Performance; Sustainability